EFFECT OF EDUCATION LEVELS OF PARENTS ON LEARNING ACHIEVEMENT OF CHILDREN IN SCHOOL (Study On Outstanding Child In SMAN 3 Banda Aceh) - Yunika Yunika; Zulfan Zulfan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRAK Perkembangan jaman di dunia pendidikan yang terus berubah dengan signifikan sehingga banyak merubah pola pikir yang awam dan kaku menjadi  modern .Tujuan pendidikan sendiri ialah menciptakan seseorang yang berkualitas dan berkarakter sehingga memiliki pandangan yang luas kedepan untuk mencapai suatucita-cita yang di harapkan dan mampu beradaptasi secara cepat dan tepat dalam berbagai lingkungan. Lingkungan keluarga atau orang tua merupakan pusat pendidikan yang pertama dan utama dalam pendidikan seorang anak, dimana kemampuan dalam mendidik anak bagi orang tua sangat tergantung dari pendidikan orang tua sendiri dalam pemberian pembelajaran materi sekolah kepada anak mereka. Dalam penelitian ini bertujuan untuk menegetahui   Pengaruh Tingkat Pendidikan Orang Tua Terhadap Prestasi Belajar Siswa di SMA N 3 Banda Aceh. Pengumpulan data dengan metode kuesioner atau angket dan metode dokumentasi, baik data pendidikan orang tuamaupun data prestasi belajar siswa. Kesimpulan dalam penelitian ini dapat disimpulkan sebagai berikut: (1) Tingkat pendidikantertinggi Ayah dari siswa-siswi berprestasi di SMAN 3 Banda Aceh adalah sarjana, yaitu sebanyak 37%. (2) Tingkat pendidikan tertinggi Ibu dari siswa-siswi berprestasi di SMAN 3 Banda Aceh adalah Diploma, yaitu sebanyak 37%. (3) Pekerjaan Ayah dari siswa-siswi berprestasi di SMAN 3 Banda Aceh adalah sebagai PNS 43%.(4) Pekerjaan Ibu dari siswa-siswi berprestasi di SMAN 3 Banda Aceh adalah PNS dan IRT, yaitu sebanyak 41%. (5) Tidak ada hubungan yang signifikan antara siswa berprestasi di SMAN 3 Banda Aceh dengan tingkat pendidikan orang tua. Hal iniberarti tidak ada hubungan yang signifikan antara siswa berprestasi di SMA N 3 Banda Aceh dengan pendidikan orang tua.Kata kunci : Tingkat Pendidikan Orang Tua, Prestasi Belajar. ABSTRACT The development of the era in the world of education is constantly changing significantly, so much to change the mindset of the layman and rigid to be modern. The goal of education itself is to create a quality person and character so that has a broad view of the fore to achieve suatucita expected and able to adapt in a fast and precise in various environments. The family or parent environment is the first and foremost center of education in a child's education, where the ability to educate children for parents is dependent on their own parents' education in providing school material to their children. In this study aims to determine the Effect of Parents Education Level on Student Achievement Achievement in SMA N 3 Banda Aceh. Data collection by questionnaire or questionnaire method and documentation method, both student's education data and student achievement data. The conclusions in this study can be summarized as follows: (1) Highest educational level Fathers of outstanding students in SMAN 3 Banda Aceh is bachelor, that is as much as 37%. (2) The highest level of Mother's education from high achieving students in SMAN 3 Banda Aceh is Diploma, which is 37%. (3) Fathers' work of outstanding students in SMAN 3 Banda Aceh is as civil servant 43%. (4) Mother's work of outstanding students in SMAN 3 Banda Aceh is civil servants and IRT, which is 41%. (5) There is no significant relationship between high achieving students in SMAN 3 Banda Aceh with parental education level. This means there is no significant relationship between high achieving students in SMA N 3 Banda Aceh with the education of parents. Keywords: Level of Parent Education, Learning Achievement.ABSTRACT  With the development of the era in the world of education that continues to change significantly, so much to change the mindset of the lay and rigid to be modern. The goal of education itself is to create a quality person and character so that has a broad view of the fore to achieve a goal that is expected and able to adapt quickly and precisely in various environments. The family or parent environment is the first and foremost center of education in a child's education, where the ability to educate children for parents is dependent on their own parents' education in providing school material to their children. In this study aims to determine (1) How the influence of parental education level on student achievement in SMA N 3 Banda Aceh. (2) To know the difference of parent role based on low and high education level on student achievement in SMA N 3 Banda Aceh. Data collection by questionnaire or questionnaire method and documentation method, both parent education data and student achievement data. The conclusions in this study can be summarized as follows: (1) The highest level of education Fathers of outstanding students in SMAN 3 Banda Aceh is bachelor, ie as much as 37%. (2) The highest level of Mother's education from high achieving students in SMAN 3 Banda Aceh is Diploma, which is 37%. (3) Fathers' work of outstanding students in SMAN 3 Banda Aceh is as civil servant 43%. (4) Mother's work of outstanding students in SMAN 3 Banda Aceh is civil servants and IRT, which is 41%. (5) There is no significant relationship between high achieving students in SMAN 3 Banda Aceh with parental education level. (1) This means there is no significant relationship between high achieving students in SMA N 3 Banda Aceh with parental education. (2) The role of highly educated parents with poorly educated parents on student achievement of SMAN 3 Banda Aceh is the same. Keywords: Level of Parent Education, Learning Achievement.